2001
DOI: 10.1177/089198870101400308
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Imaging and Magnetic Resonance Spectroscopy in Dementias

Abstract: This article reviews recent studies of magnetic resonance imaging and magnetic resonance spectroscopy in dementia, including Alzheimer's disease, frontotemporal dementia, dementia with Lewy bodies, idiopathic Parkinson's disease, Huntington's disease, and vascular dementia. Magnetic resonance imaging and magnetic resonance spectroscopy can detect structural alteration and biochemical abnormalities in the brain of demented subjects and may help in the differential diagnosis and early detection of affected indiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
4

Year Published

2002
2002
2007
2007

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 297 publications
(223 reference statements)
0
20
0
4
Order By: Relevance
“…A aplicação de técnicas de neuroimagem tem possibilitado investigar a presença de alterações cerebrais in vivo em amostras de portadores de transtornos neuropsiquiátricos comparados a grupos controle de voluntários saudáveis pareados para variáveis demográficas, com qualidade crescente de sensibilidade e resolução anatômica (Hsu et al, 2001). Técnicas como a tomografia computadorizada (TC) e a RM fornecem dados sobre a anatomia estrutural do cérebro, permitindo a detecção de lesões circunscritas ou difusas, ou a avaliação quantitativa do volume de diferentes estruturas cerebrais.…”
Section: Neuroimagem E Demênciasunclassified
“…A aplicação de técnicas de neuroimagem tem possibilitado investigar a presença de alterações cerebrais in vivo em amostras de portadores de transtornos neuropsiquiátricos comparados a grupos controle de voluntários saudáveis pareados para variáveis demográficas, com qualidade crescente de sensibilidade e resolução anatômica (Hsu et al, 2001). Técnicas como a tomografia computadorizada (TC) e a RM fornecem dados sobre a anatomia estrutural do cérebro, permitindo a detecção de lesões circunscritas ou difusas, ou a avaliação quantitativa do volume de diferentes estruturas cerebrais.…”
Section: Neuroimagem E Demênciasunclassified
“…The number of CAG repeats, as one study showed, may aid in the prediction of age of onset and penetrance of HD [81]. For instance, for a 41-year-old individual who has 42 CAG repeats, it predicts a 91 % chance that the individual will have HD onset by the age of 65 [82]. Onset of the disease may be different but usually comes up in midlife, depending on both sex and age.…”
Section: Huntington's Disease (Hd)mentioning
confidence: 99%
“…Imaging technologies offer great promise in identifying biomarkers. These modalities include PET and nuclear magnetic resonance spectroscopy (NMRS) [82,83]. Animal and human studies of biomarkers should be run in parallel and compared with each other in order to take advantage of advances being made in animal models to understand the mechanisms of disease.…”
Section: Huntington's Disease (Hd)mentioning
confidence: 99%
“…8,9 Many single voxel (SV) MRS and multivoxel magnetic resonance spectroscopic imaging (MRSI) studies have shown reduced NAA in AD, especially in hippocampus and parietal lobe, with lesser reductions in frontal lobe. 10,11 mI has been suggested as a glial marker 12,13 and, in contrast to NAA, is increased in AD. 14,15 Many SV MRS studies showed increased mI 16-23 associated with decreased NAA [16][17][18][19][20][23][24][25][26] in AD.…”
mentioning
confidence: 99%